The Influence of Business Capital and Financial Literacy on the Sustainability of MSMEs - Deviyanti, Veronica Astrid; Rahadjeng, Erna Retna; Sudiyono, Widhiyo (Jurnal Manajemen Bisnis dan Kewirausahaan, 2024)
The aim of this research is to determine the influence of business capital and financial literacy on the sustainability of MSMEs. The method used is a quantitative approach and data collection using questionnaires and multiple linear regression data analysis techniques. Apart from that, classical assumption tests, hypothetical tests, and calculation of the coefficient of determination using the SPSS 23 application were carried out. The research sample was determined as 165 MSME actors in the Tugu District in the food sector. and drinks. The sampling technique used the proportional stratified random sampling method. The research results show that the business capital variable has a positive and significant effect on the sustainability of MSMEs. The financial literacy variable has a positive and significant effect on the sustainability of MSMEs. The variables of business capital and financial literacy simultaneously have a positive and significant effect on the sustainability of MSMEs.